The Role of Farmer Groups in Preventing Corruption of Village Funds (A Case Study in Lamongan Regency): The Role of Farmer Groups in Preventing Corruption of Village Funds (A Case Study in Lamongan Regency) - Sundari, Ariefah; Muslikh; Kuncoro, Cipto; Moh. Hudi; Afiyah, Siti (Fakultas Hukum Universitas Tompotika Luwuk Banggai, 2025)
This study aims to analyze the role of farmer groups in preventing corruption of village funds, using a case study in Manyar Village, Lamongan Regency. The research employs a combination of normative and empirical legal approaches by examining relevant legal regulations and field findings based on direct community involvement. The results reveal that while the disbursement and use of village funds procedurally comply with existing laws, community participation in budget oversight remains limited. Farmer groups, traditionally perceived as agricultural production units, have demonstrated potential as informal agents in monitoring village projects. These findings indicate that their involvement in verifying physical project implementation and reporting discrepancies has helped reduce the risk of corruption. The scientific contribution of this research lies in recognizing local actors as key players in participatory governance and grassroots-based integrity systems. The study advocates for policy reforms that formally integrate farmer groups into village fund oversight frameworks to promote greater transparency and accountability in rural financial governance.